1990
DOI: 10.1105/tpc.2.6.581
|View full text |Cite
|
Sign up to set email alerts
|

Identification and molecular characterization of shrunken-2 cDNA clones of maize.

Abstract: Mutation at the shrunken-2 (Sh2) locus of maize, a gene described more than 40 years ago, greatly reduces starch levels in the endosperm through its effect on the starch synthetic enzyme ADP-glucose pyrophosphorylase, an enzyme thought to be regulatory in this biosynthetic pathway. Although our previous work has suggested that Sh2 is a structural gene for this enzyme, we have also reported data compatible with Sh2 acting post-transcriptionally.In this study, we took advantage of a transposable element-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
128
0
3

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(136 citation statements)
references
References 21 publications
5
128
0
3
Order By: Relevance
“…Cloning and sequencing of Sh2 and Bt2 and analysis of informative mutants (Bae et al, 1990, Bhave et al, 1990) of maize endosperm transcripts and genes showed that both loci encode subunits of AGP. Bt2 encodes the small subunit, whereas the large subunit is derived from Sh2.…”
mentioning
confidence: 99%
“…Cloning and sequencing of Sh2 and Bt2 and analysis of informative mutants (Bae et al, 1990, Bhave et al, 1990) of maize endosperm transcripts and genes showed that both loci encode subunits of AGP. Bt2 encodes the small subunit, whereas the large subunit is derived from Sh2.…”
mentioning
confidence: 99%
“…Sh2 encodes a subunit of endosperm ADP-glucose pyrophosphorylase, the key enzyme for starch biosynthesis in maize endosperm (Bhave et al 1990). Mutations in Sh2 result in a great reduction in starch levels with concomitantly high sucrose accumulation.…”
Section: Glucan Accumulation Analysis In Mature Transgenic Seedsmentioning
confidence: 99%
“…Lal et al (2003) found the Helitron -like element within the Shrunken2 ( Sh2 ) gene in the mutant sh2-7527 , which appears to have arisen spontaneously in a conventional maize breeding program in the 1970s. sh2 mutants are characterized by kernels with poorly developed, shrunken endosperm tissue (Figure 1), resulting from mutations in the Sh2 gene, which encodes the large subunit of ADP-Glc pyrophosphorylase (Bhave et al, 1990). The Sh2 protein is a key enzyme in starch biosynthesis and is produced exclusively in the endosperm; sh2 mutants contain a much lower concentration of starch and a much higher concentration of Suc than the wild type.…”
Section: In This Issuementioning
confidence: 99%